Spatial Estimation of Regional Economic Growth Heterogeneity During 2014‒2021 - Svetlana V. Doroshenko; Rogneda I. Vasilyeva (Регионология, 2024)
Introduction. The aggravation of socio-economic heterogeneity among Russian regions is one of the main challenges for sustainable development of the country. The main task of spatial policy is to ensure advanced rates of development of geostrategic and lagging behind territories as well as increasing competitiveness of regional economies. However, the events of the past decade substantially adjusted plans on regional economic growth enhancement. The aim of the study is to estimate spatial economic growth heterogeneity and interdependence of bordering entities of Russia over 2013‒2021.